Analysis Of Internal Control In The Supply Of Raw Materials In The Dusun Coffee Business In Talang Benuang Village Sukaraja District Seluma District - Rita Resmaini; Yun Fitriano; Abdul Rahman (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This research aims to determine the application of internal control in the supply of raw materials for the Dusun coffee business as well as COSO analysis of the internal control system in the Dusun coffee business. In this research, researchers used descriptive qualitative methods with a case study approach. Data collection was carried out by means of observation and interviews. The data that has been collected is then processed and analyzed. The results of research conducted in the Dusun coffee business regarding the implementation of internal control on raw material supplies for the Dusun coffee business showed that internal control over inventory in the Dusun coffee business was less effective, and there were no recording activities and related documents such as stock taking.